Human Resource Competence as a Moderating Variable for the Quality of Local Government Financial Reports - Lativa Ulisanti; Asrori Asrori (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The autonomy policy has urged local governments in Indonesia to have better governance to support local finance management. Local governments are demanded to present quality financial reports—this has been such a challenge for many local governments. This study aimed to analyze the effect of an effective internal control system and utilization of information technology on the quality of local government financial reports, moderated by human resource competence. The study’s population and samples were the heads and treasury of the financial department from all work units in Grobogan Regency, Central Jawa. Samples were chosen through a purposive sampling method. Data from 98 respondents were analyzed using SPSS Version 25.0. Data collected were the primary data from questionnaires. Items in the questionnaire were presented using the Likert Scale with five provided alternatives. Data were analyzed using descriptive statistic methods and regression analysis for the moderation effect with absolute difference tests. Findings showed that the effectiveness of the internal control system and the utilization of information technology partially had a positive and significant effect on the quality of local government financial reports. Hypothesis testing confirmed that human resource competence strengthened the effect of utilization of information technology on the quality of local government financial reports, yet weakened the effect of the internal control system on the quality of local government financial reports. Keywords: Financial Reports, Internal Control Systems, Information Technology, Human Resources.